The Nuclear Matrix Protein Megator Regulates Stem Cell Asymmetric Division through the Mitotic Checkpoint Complex in Drosophila Testes. - Ying Liu; Shree Ram Singh; Xiankun Zeng; Jiangsha Zhao; Steven X Hou (PLoS Genetics)
In adult Drosophila testis, asymmetric division of germline stem cells (GSCs) is specified by an oriented spindle and cortically localized adenomatous coli tumor suppressor homolog 2 (Apc2). However, the molecular mechanism underlying these events remains unclear. Here we identified Megator (Mtor), a nuclear matrix protein, which regulates GSC maintenance and asymmetric division through the spindle assembly checkpoint (SAC) complex. Loss of Mtor function results in Apc2 mis-localization, incorrect centrosome orientation, defective mitotic spindle formation, and abnormal chromosome segregation that lead to the eventual GSC loss. Expression of mitotic arrest-deficient-2 (Mad2) and monopolar spindle 1 (Mps1) of the SAC complex effectively rescued the GSC loss phenotype associated with loss of Mtor function. Collectively our results define a new role of the nuclear matrix-SAC axis in regulating stem cell maintenance and asymmetric division.